Pregnancy after kidney transplantation: an observational study on maternal, graft and offspring outcomes in view of current literature - Stavart, Louis; Verly, Camille; Venetz, Jean-Pierre; Baud, David; Legardeur, Helene; Vial, Yvan; Golshayan, Dela (Frontiers in Nephrology, 2023)
Pregnancy after kidney transplantation (KTx) is considered high risk with non-negligible potential complications for the mother, allograft, and the offspring. With an increased incidence of those pregnancies over the past decades, transplant nephrologists and specialized obstetricians face increasing challenges within the framework of scarce literature regarding long-term outcomes. We retrospectively collected data from women with at least one live birth pregnancy after KTx, followed in our tertiary hospital between 2000 and 2021, to study maternal, graft and fetal outcomes. Ten patients were accountable for 14 live birth pregnancies after KTx. Preponderant maternal complications were stage 1 acute kidney injury (43%), urinary tract infections (UTI, 43%), progression of proteinuria without diagnostic criteria for preeclampsia (29%), and preeclampsia (14%). Median baseline serum creatinine at conception was 126.5 mol/L (median estimated glomerular filtration rate (eGFR) 49 mL/min/1.73m 2 ), and eGFR tended to be lower than baseline at follow-ups. Overall, there was no increase in preexisting or occurrence of de novo donor-specific antibodies. No graft loss was documented within the 2-year follow-up. There were nine premature births (64%), with a median gestational age of 35.7 weeks. The median birth weight, height and head circumference were 2560 grams, 45.5 centimeters, and 32.1 centimeters, respectively. These measurements tended to improve over time, reaching a higher percentile than at birth, especially in terms of height, but on average remained under the 50th percentile curve. Overall, pregnancies after KTx were at risk for the mother, with a high prevalence of caesarean sections, emergency deliveries, UTI, and preeclampsia; and for the child with a high proportion of prematurity, lower measurements at birth, and a tendency to stay under the 50 th percentile in growth charts. The short and long-term impact on the allograft seemed reassuring with however a trend towards lower eGFR after pregnancy. With these data, we emphasize the need for a careful examination of individual risks with specialized pre-conception consultations and a regular monitoring by a transplant nephrologist and a specialist in maternal-fetal medicine during pregnancy. More data about the long-term evolution of children are required to fully apprehend the impact of KTx on the offspring.